Central nervous system demyelinating diseases: glial cells at the hub of pathology - Coutinho Costa, Vinicius Gabriel; Araújo, Sheila Espírito-Santo; Alves-Leon, Soniza Vieira; Gomes, Flávia Carvalho Alcantara (Frontiers in Immunology, 2023)
Idiopathic inflammatory demyelinating diseases (IIDDs) are among the main causes of inflammatory central nervous system injury in young adult patients. Of these, multiple sclerosis (MS) is the most studied, as it affects about a million people in the USA alone. The understanding of the mechanisms underlying their pathology has been advancing, although there are still no highly effective disease-modifying treatments for the progressive symptoms and disability in the late stages of disease. Among these mechanisms, the action of glial cells upon lesion and regeneration has become a prominent research topic, helped not only by the discovery of glia as targets of autoantibodies, but also by their role CNS homeostasis e neuroinflammation. In the present article, we discuss the participation of glial cells in IIDDS, as well as their association with demyelination and synaptic dysfunction throughout the course of the disease and in experimental models, with a focus on MS phenotypes. We discuss the involvement of microglia and astrocytes in lesion formation and organization, remyelination, synaptic induction and pruning through different signaling pathways. We argue that evidence of the several glia-mediated mechanisms in the course of demyelinating diseases supports them as viable targets for therapy development.